Targeted Quantification of Phosphorylation Sites Identifies STRIPAK-Dependent Phosphorylation of the Hippo Pathway-Related Kinase SmKIN3 - Valentina Stein; Bernhard Blank-Landeshammer; Ramona Märker; Albert Sickmann; Ulrich Kück (mBio, 2021)
Phosphorylation and dephosphorylation of proteins are fundamental posttranslational modifications that determine the fine-tuning of their biological activity. Involved in this modification process is the recently identified stripak